Dynamics of changes in nonspecific resistance of guinea pigs under conditions of formation of experimental periodontitis and immobilization stress - P. Olekshij (Kazimierz Wielki University, 2021)
The aim of our study was to determine the phagocytic activity of leukocytes and nitrosine tetrazolium test (NST - test) in the dynamics of experimental periodontitis (EP) and immobilization stress (IS). It is established in the work that the indicators studied by us, namely phagocytic number, phagocytic index and NST - test increase on the 3 rd, 5 th and 15 th days of our experiment. The above tests have a high diagnostic value and allow to characterize the degree of activity of the inflammatory process and determine the participation of individual parts of the body's defense mechanisms. The obtained results make it possible to express the opinion that polymorphonuclear leukocytes take an active part in the formation of EP and IS, as well as indicate the stimulation of metabolic processes in leukocytes.